Oncogenic roles of enhancer of zeste homolog 1/2 in hematological malignancies. Issue 8 (27th June 2018) - Nakagawa, Makoto; Kitabayashi, Issay
Abstract : Polycomb group (PcG) proteins regulate the expression of target genes by modulating histone modifications and are representative epigenetic regulators that maintain the stemness of embryonic and hematopoietic stem cells. Histone methyltransferases enhancer of zeste homolog 1 and 2 (EZH1/2), which are subunits of polycomb repressive complexes (PRC), are recurrently mutated or highly expressed in many hematological malignancies. EZH2 has a dual function in tumorigenesis as an oncogene and tumor suppressor gene, and targeting PRC2, in particular EZH1/2, for anticancer therapy has been extensively developed in the clinical setting. Here, we review the oncogenic function of EZH1/2 and introduce new therapeutic drugs targeting these enzymes. Abstract : Histone methyltransferases enhancer of zeste homolog 1 and 2 (EZH1/2), which are subunits of polycomb repressive complexes (PRC), are recurrently mutated or highly expressed in many hematological malignancies. EZH2 has a dual function in tumorigenesis as an oncogene and as a tumor suppressor gene, and targeting PRC2, in particular EZH1/2, for anticancer therapy has been extensively developed in the clinical setting.